Auditory complications among childhood cancer survivors and health-related quality of life: a PanCareLIFE study - Strebel, Sven; Baust, Katja; Grabow, Desiree; Byrne, Julianne; Langer, Thorsten; Am Zehnhoff-Dinnesen, Antoinette; Kuonen, Rahel; Weiss, Annette; Kepak, Tomas; Kruseova, Jarmila; Berger, Claire; Calaminus, Gabriele; et al. (Journal of cancer survivorship, 2025)
PURPOSE: Auditory complications are potential side effects from childhood cancer treatment. Yet, limited evidence exists about the impact of auditory complications-particularly tinnitus-on health-related quality of life (HRQoL) among childhood cancer survivors (CCS). We determined the prevalence of hearing loss and tinnitus in the European PanCareLIFE cohort of CCS and examined its effect on HRQoL. METHODS: We included CCS from four European countries who were diagnosed at age ≤ 18 years; survived ≥ 5 years; and aged 25-44 years at study. We assessed HRQoL (Short Form 36), hearing loss, and tinnitus using questionnaires. We used multivariable linear regression to examine associations between these two auditory complications and HRQoL adjusting for socio-demographic and clinical factors. RESULTS: Our study population consisted of 6,318 CCS (53% female; median age at cancer diagnosis 9 years interquartile range [IQR] 5-13 years) with median age at survey of 31 years (IQR 28-35 years). Prevalence was 7.5% (476/6,318; confidence interval [CI]: 6.9-8.2) for hearing loss and 7.6% (127/1,668; CI: 6.4-9.0) for tinnitus. CCS with hearing loss had impaired physical (coefficient [coef.] -4.3, CI: -7.0 to -1.6) and mental (coef. -3.2, CI: -5.5 to -0.8) HRQoL when compared with CCS with normal hearing. Tinnitus was associated with impaired physical (coef. -8.2, CI: -11.8 to -4.7) and mental (coef. -5.9, CI: -8.8 to -3.1) HRQoL. CONCLUSION: We observed reduced HRQoL among CCS with hearing loss and tinnitus. Our findings indicate timely treatment of hearing loss and tinnitus may contribute to quality of life of survivors. IMPLICATIONS FOR CANCER SURVIVORS: CCS who experience auditory complications should be counseled about possible therapeutic and supportive measures during follow-up care.
Keywords: nedoslýchavost; Hearing Loss; lidé; mladiství; Adult; přežívající onkologičtí pacienti; Female; dítě; průzkumy a dotazníky; Evropa; Prevalence; Survivorship; Tinnitus; Childhood cancer; tinnitus; Surveys and Questionnaires; Quality of Life; Adolescent; Humans; Quality of life; předškolní dítě; Child, Preschool; mužské pohlaví; mladý dospělý; Cancer Survivors; nádory; Hearing loss; ženské pohlaví; prevalence; Young Adult; kvalita života; Male; Europe; Child; dospělí; Neoplasms